Treatment liquid for resin printing plate, resin printing plate using the same and method for manufacturing printed matter

JP2025035959APending Publication Date: 2025-03-14TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023174105
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2023-10-06
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0008】 本発明の印刷版用処理液によれば、異物による印刷抜けが生じにくい、印刷性に優れた樹脂印刷版を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035959000001
    Figure 2025035959000001
  • Figure 2025035959000002
    Figure 2025035959000002
Patent Text Reader

Abstract

To provide a treatment liquid for a resin printing plate which dispenses with an organofluorine compound, prevents printing omission by a foreign matter, and enables provision of a resin printing plate excellent in printability.SOLUTION: A treatment liquid for a resin printing plate contains a metal chelate compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a treatment liquid for a resin printing plate, and a method for producing a resin printing plate and a printed matter using the same. [Background technology]

[0002] Letterpress printing, such as flexographic printing and resin letterpress printing, is widely used for paper containers, labels, soft packaging, electronics, etc. Resin letterpress printing is a printing method in which ink is applied to the apexes of the raised relief of a resin printing plate and the relief is pressed against the substrate, thereby transferring the ink from the relief to the substrate. If foreign matter such as dust, dirt, or paper powder adheres to the relief at this time, the ink does not adhere to the area around the foreign matter, so the ink is not transferred to the substrate, resulting in a printing defect called a print defect.

[0003] Therefore, as a technology for reducing adhesion of foreign matter such as dust, dirt, and paper powder to the relief, a plate surface treatment liquid containing a fluorine-containing polymer having perfluoroalkyl groups with an average carbon number of 7 or less has been proposed for treating the plate surface of a photosensitive resin plate or letterpress printing plate having an uneven surface (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2008 / 133055 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, in consideration of the impact on the environment and human health, there has been an international movement to restrict the use of artificially produced organic fluorine compounds (PFAS), which are difficult to decompose in nature, and there is a demand for a processing liquid that does not use organic fluorine compounds, as an alternative to the plate surface processing liquid described in Patent Document 1.

[0006] In view of the above problems, an object of the present invention is to provide a treatment liquid for a resin printing plate, which does not require an organic fluorine compound and can provide a resin printing plate having excellent printability and which is less susceptible to printing defects caused by foreign matter. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention mainly has the following configuration. (1) A processing solution for resin printing plates containing a metal chelate compound. (2) The processing liquid for resin printing plates according to (1), which contains a titanium chelate compound as the metal chelate compound. (3) The treatment liquid for resin printing plates according to (2), which contains as the titanium chelate compound titanium diisopropoxide bis(triethanol aminate), titanium di-n-butoxide bis(triethanol aminate), titanium diisopropoxide bis(ethylacetoacetate), titanium dihydroxybis(lactate), titanium dihydroxybis(ammonium lactate), titanium aminoethylaminoethanolate and / or titanium(ethylene glycolate) bis(dioctyl phosphate). (4) The processing liquid for resin printing plates according to any one of (1) to (3), which contains the metal chelate compound in an amount of 0.1% by weight or more and 50% by weight or less. (5) A method for producing a resin printing plate, comprising the steps of partially removing a relief-forming layer of a resin printing plate precursor having a relief-forming layer on a support to form a relief, and contacting at least a portion of the relief with a treatment liquid for a resin printing plate according to any one of (1) to (4). (6) A method for producing a resin printing plate according to (5), in which in the step of contacting at least a part of the relief with the treatment liquid for a resin printing plate according to any one of (1) to (4), a coating roller is used to contact at least a part of the relief with the treatment liquid for a resin printing plate. (7) A method for producing a printed matter, comprising the steps of obtaining a resin printing plate by the method according to (5) or (6), depositing ink on the relief, and transferring the ink to a substrate. (8) The method for producing a printed matter according to (7), wherein the ink is an ultraviolet-curable ink and / or an electron beam-curable ink. Effect of the Invention

[0008] The printing plate treating liquid of the present invention makes it possible to obtain a resin printing plate having excellent printability and which is less susceptible to printing voids caused by foreign matter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The treatment liquid for resin printing plates according to the present invention (hereinafter sometimes abbreviated as "treatment liquid") is suitable for use in letterpress printing plates such as resin letterpress printing plates and flexographic printing plates, and is particularly suitable for use in flexographic printing plates which have a soft relief and are susceptible to foreign matter adhesion. The relief of these resin printing plates generally has hydroxyl groups and carboxyl groups derived from binder resins or the like.

[0010] The treatment liquid of the present invention contains a metal chelate compound, which reacts with hydroxyl groups and / or carboxyl groups in the relief to form a crosslinked structure by covalent bond, thereby suppressing the adhesion of the relief to dust, dirt, paper powder, etc., which are foreign matters that cause printing defects.

[0011] Examples of the metal chelate compound include an aluminum chelate compound, a titanium chelate compound, a zirconium chelate compound, etc. Two or more of these may be contained.

[0012] Examples of the ligand that forms a chelate include β-diketones such as acetylacetone, β-ketoesters such as ethyl acetoacetate, propyl acetoacetate, butyl acetoacetate, hexyl acetoacetate, and nonyl acetoacetate, alkanolamines such as diethanolamine and triethanolamine, glycols such as octylene glycol and octanediol, hydroxycarboxylic acids such as lactic acid, citric acid, and malic acid, and ammonium salts thereof, etc. Two or more of these may be used.

[0013] Examples of aluminum chelate compounds include aluminum tris(acetylacetonate), aluminum tris(ethylacetoacetate), aluminum tris(propylacetoacetate), aluminum tris(butylacetoacetate), aluminum tris(hexylacetoacetate), aluminum tris(nonylacetoacetate), aluminum tris(2,2,6,6-tetramethyl-3,5-heptanedionate), aluminum bis(ethylacetoacetate) mono(acetylacetonate), aluminum bis(acetylacetonate) mono(ethylacetoacetate), aluminum bis(propylacetoacetate) mono(acetylacetonate), aluminum bis(butylacetoacetate) mono(acetylacetonate), aluminum bis(hexylacetoacetate) mono(acetylacetonate). Examples of aluminum chelate compounds include aluminum bis(propylacetoacetate) mono(ethylacetoacetate), aluminum bis(butylacetoacetate) mono(ethylacetoacetate), aluminum bis(hexylacetoacetate) mono(ethylacetoacetate), aluminum bis(nonylacetoacetate) mono(ethylacetoacetate), aluminum dibutoxide mono(acetylacetonate), aluminum diisopropoxide mono(acetylacetonate), aluminum diisopropoxide mono(ethylacetoacetate), aluminum-s-butoxide bis(ethylacetoacetate), aluminum di-s-butoxide mono(ethylacetoacetate), and aluminum diisopropoxide mono(-9-octadecenylacetoacetate).

[0014] Examples of titanium chelate compounds include titanium triisopropoxide mono(allyl acetoacetate), titanium diisopropoxide bis(triethanol aminate), titanium di-n-butoxide bis(triethanol aminate), titanium diisopropoxide bis(acetylacetonate), titanium di-n-butoxide bis(acetylacetonate), titanium diisopropoxide bis(2,2,6,6-tetramethyl-3,5-heptanedionate), titanium diisopropoxide bis(ethyl acetoacetate), titanium di-n-butoxide bis(ethoxyacetate). Examples of titanium chelate compounds include titanium tri-n-butoxide mono(ethyl acetoacetate), titanium triisopropoxide mono(methacryloxyethyl acetoacetate), titanium oxide bis(acetylacetonate), titanium tetra(2-ethyl-3-hydroxyhexyl oxide), titanium dihydroxybis(lactate), titanium dihydroxybis(ammonium lactate), titanium aminoethyl aminoethanolate, and titanium (ethylene glycolate) bis(dioctyl phosphate).

[0015] Examples of zirconium chelate compounds include zirconium di-n-butoxide bis(acetylacetonate), zirconium tri-n-propoxide mono(methacryloxyethyl acetoacetate), zirconium tetrakis(acetylacetonate), and zirconium tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionate).

[0016] Among these, titanium chelate compounds are preferred from the viewpoint of storage stability of the processing solution and high reactivity with the relief.When the processing solution contains water together with the metal chelate compound, water-soluble titanium chelate compounds are more preferred.Examples of water-soluble titanium chelate compounds include titanium diisopropoxide bis(triethanolamine), titanium di-n-butoxide bis(triethanolamine), titanium diisopropoxide bis(ethylacetoacetate), titanium dihydroxybis(lactate), titanium dihydroxybis(ammonium lactate), titanium aminoethylaminoethanolate, and titanium(ethylene glycolate)bis(dioctyl phosphate).

[0017] The content of the metal chelate compound in the treatment liquid is preferably 0.1% by weight or more, more preferably 1.0% by weight or more, and even more preferably 2.0% by weight or more, from the viewpoints of further suppressing adhesion of dust, dirt, paper powder, etc., which cause printing defects due to foreign matter, to the relief and further improving printability. On the other hand, the content of the metal chelate compound is preferably 50% by weight or less, more preferably 25% by weight or less, and even more preferably 10% by weight or less, from the viewpoints of reducing the viscosity of the treatment liquid and economic efficiency.

[0018] The treatment liquid may further contain, as necessary, water, water-soluble solvents such as ethers, esters, alcohols, and ketones, dyes, pigments, defoamers, ink repellents, fragrances, etc. Here, from the viewpoint of drying properties of the treatment liquid, it is more preferable that the solvent contains an organic solvent such as alcohol. Also, from the viewpoints of flammability and safety to the human body, it is preferable that the treatment liquid further contains water.

[0019] Next, a method for producing a resin printing plate according to the present invention will be described. The method for producing a resin printing plate according to the present invention includes a step of forming a relief by partially removing a relief-forming layer of a resin printing plate precursor having a relief-forming layer on a support (a relief-forming step), and a step of contacting the relief with the above-mentioned processing liquid (a processing step).

[0020] The resin printing plate precursor preferably has at least a support and a relief-forming layer in this order, and the relief-forming layer is a layer that becomes a relief in the resin printing plate. Examples of the relief-forming layer include a photosensitive resin layer that undergoes polymerization by absorption of electromagnetic energy rays such as ultraviolet light and becomes insoluble in a developer, and a resin layer that can be engraved into a desired shape by electromagnetic energy rays such as laser light. The photosensitive resin layer can form a desired relief by, for example, irradiating it with ultraviolet light imagewise. Among these, a photosensitive resin layer that can be developed with water is preferred from the viewpoints of environmental load, productivity of the printing plate, and image reproducibility.

[0021] The water-developable photosensitive resin layer preferably contains, as a binder resin, a partially saponified polyvinyl alcohol having a hydrophilic group such as a hydroxyl group or a carboxyl group. Examples of resin printing plate precursors having a photosensitive resin layer containing such a binder resin include the photosensitive resin printing plate precursors described in WO 2018 / 088336.

[0022] Examples of the relief forming step include a method of engraving a relief forming layer into a desired shape by electromagnetic energy rays such as laser light, and when the relief forming layer is a photosensitive resin layer, a method having an exposure step of partially photocuring the photosensitive resin layer and a development step of removing uncured parts of the photosensitive resin layer with a developer, etc. Among these, from the viewpoints of productivity and image reproducibility of the printing plate, a method having an exposure step and a development step using a photosensitive resin layer as the relief forming layer is preferred.

[0023] First, the exposure step will be described. In the case where the printing plate precursor has a heat-sensitive mask layer, that is, a so-called CTP plate, the cover film is peeled off if it has one, and an image corresponding to the original film is drawn using a laser drawing machine, and then the photosensitive resin layer is photocured by irradiating it with ultraviolet light. In the case where the printing plate precursor does not have a heat-sensitive mask layer, the photosensitive resin layer is photocured by irradiating it with ultraviolet light through the original film. As the ultraviolet light, light with a wavelength of 300 to 400 nm is preferable, and examples of lamps used for ultraviolet light irradiation include high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, carbon arc lamps, and chemical lamps. In particular, when reproducibility of fine thin lines and independent points is required, it is also possible to form a floor layer by short-time exposure (back exposure) from the support side before peeling off the cover film.

[0024] Next, the developing step will be described. The exposed printing plate precursor is immersed in a developer, and the uncured portion of the photosensitive resin layer is removed by the developer using a brush-type developer or a spray-type developer, thereby forming a relief image on the substrate. The developer preferably contains water, and may contain additives as necessary. The developer temperature during development is preferably 15 to 40°C.

[0025] After development, it is preferable to dry the film for about 10 minutes at 50 to 70° C. If necessary, post-exposure may be performed by irradiating the film with actinic rays in the atmosphere or in a vacuum.

[0026] Next, the processing step will be described. The processing step is preferably carried out after the relief forming step, but may be carried out before the above-mentioned drying or post-exposure. In addition, the developing step and the processing step may be carried out simultaneously by using a processing solution as a developer in the developing step.

[0027] Examples of methods for contacting the relief with the treatment liquid include a method using the treatment liquid as a developer in the development step, a method immersing the formed relief in the treatment liquid, a method wiping the relief with a sponge or cloth soaked in the treatment liquid, a method spraying the treatment liquid onto the relief, and a method applying the treatment liquid onto the relief using a coating roller. These methods may be performed continuously or batchwise. Among these, the method of applying the treatment liquid onto the relief using a coating roller is preferably used from the viewpoints of selectively processing only the relief of the printing plate, suppressing scattering of the treatment liquid mist, and shortening the treatment time.

[0028] The coating roller preferably has a structure capable of retaining the treatment liquid around the rotating core material. Examples of the structure include a sponge structure and a fibrous structure.

[0029] The sponge structure preferably has open cells. Examples of the material of the sponge structure include polyurethane, polyvinyl alcohol, polyolefin (polyethylene, polypropylene), vinyl chloride, ethylene-vinyl acetate copolymer, cellulose, and sponge. Two or more of these may be used. Among these, polyurethane, polyolefin (polyethylene, polypropylene), and ethylene-vinyl acetate copolymer are preferred from the viewpoint of chemical resistance to organic solvents and maintaining elasticity in a dry state.

[0030] Examples of the fiber structure include woven fabrics and high-pile fabrics. Among these, woven fabrics are preferred from the viewpoint of reducing fiber shedding. Examples of the material for the fiber structure include fibers such as polyester, polyamide, polyurethane, and acrylic resin, as well as wool, hog hair, and goat hair. Two or more of these may be used. Among these, polyester and polyurethane fibers are preferred from the viewpoint of chemical resistance to organic solvents and quality stability.

[0031] The temperature of the treatment liquid in the treatment step is preferably 5° C. or higher, more preferably 10° C. or higher, from the viewpoint of suppressing precipitation of the metal chelate compound, while the temperature of the treatment liquid in the treatment step is preferably 100° C. or lower, more preferably 80° C. or lower, from the viewpoint of suppressing volatilization of the treatment liquid.

[0032] The contact time between the relief and the processing solution in the processing step is preferably 1 second or more, more preferably 5 seconds or more, from the viewpoint of further suppressing adhesion of foreign matter to the relief, whereas the contact time between the relief and the processing solution in the processing step is preferably 1 hour or less, from the viewpoint of work efficiency.

[0033] It is preferable to have a drying step for removing the treatment liquid remaining on the relief surface of the printing plate after the treatment step. In the drying step, the metal chelate compound reacts with the resin contained in the relief to form a dense film, which can further suppress adhesion of foreign matter to the relief during printing. Examples of drying methods include natural drying, air drying, heat drying, vacuum drying, and freeze drying. Among these, natural drying, which consumes less energy during drying, is preferred. Furthermore, in the case of a treatment liquid containing water, heat drying is preferred from the viewpoint of work efficiency. The heating temperature for heat drying is preferably 30° C. or higher, more preferably 40° C. or higher, from the viewpoint of drying speed. The drying time is preferably 5 minutes or longer.

[0034] Next, a method for producing a printed matter of the present invention will be described. The method for producing a printed matter of the present invention includes a step of adhering ink to the relief of the resin printing plate obtained by the above-mentioned method, and a step of transferring the ink to a printing medium. Examples of flexographic printing machines include in-line type, center drum type, and stack type.

[0035] The ink is preferably an ultraviolet curable ink or an electron beam curable ink. The ultraviolet curable ink is preferably one containing, for example, a pigment, a resin such as an acrylic oligomer, an acrylate monomer, a polymerization initiator, etc., and more specifically, for example, commercially available flexographic printing inks such as PHA (manufactured by T&K TOKA Co., Ltd.), "FLASH DRY" (registered trademark) (manufactured by Toyo Ink Co., Ltd.), and "UVAFLEX" (registered trademark) Y77 (manufactured by Zeller+Gmelin). The electron beam curable ink is preferably one containing, for example, a pigment, a resin such as an acrylic oligomer, an acrylate monomer, etc., and more specifically, for example, flexographic printing inks such as "GelFlex EB" (registered trademark) (manufactured by SAKATA INX). EXAMPLES

[0036] The materials used in each of the examples and comparative examples are shown below.

[0037] (Metal chelate compounds) "Orgatics" (registered trademark) TC-100 (titanium chelate compound, titanium diisopropoxide bis(acetylacetonate) 75% by weight in 2-propanol solution, manufactured by Matsumoto Fine Chemical Co., Ltd.) "Orgatix" (registered trademark) TC-300 (a water-soluble titanium chelate compound, a 42% by weight solution of titanium dihydroxybis(ammonium lactate), 38% by weight of 2-propanol, 20% by weight of water, manufactured by Matsumoto Fine Chemical Co., Ltd.) "Orgatix" (registered trademark) TC-400 (water-soluble titanium chelate compound, 80% by weight 2-propanol solution of titanium diisopropoxide bis(triethanolamine), manufactured by Matsumoto Fine Chemical Co., Ltd.) (others) "Orgatix" (registered trademark) TA-8 (titanium alkoxide compound, 99% by weight 2-propanol solution of tetraisopropyl titanate, manufactured by Matsumoto Fine Chemical Co., Ltd.) ·Water (high purity purified water, product number W10-A2, JIS standard A2~A3, manufactured by Trusco Co., Ltd.) 2-Propanol (2-Propanol (>99.5%), Standard: Grade 1, manufactured by Kanto Chemical Co., Ltd.).

[0038] (Paint roller) "Micro Grande" (registered trademark) 7 mm small roller (structure: polyester microfiber woven fabric, model: 4S-MG7, width: 15.2 cm (6 inches), manufactured by Otsuka Brush Manufacturing Co., Ltd.). "Piolas" (registered trademark) sponge roller (structure: open-cell polyolefin sponge, type: T-type, width: 15 cm, outer diameter: 4 cm, structure thickness: 1 cm, manufactured by AION Co., Ltd.).

[0039] (Production Example 1: Preparation of Flexographic Printing Plate Precursor 1) [Preparation of a support having a primer layer and an adhesive layer] A mixture of 260 parts by weight of "Vylon" (registered trademark) 31SS (toluene solution of saturated polyester resin, manufactured by Toyobo Co., Ltd.) and 2 parts by weight of PS-8A (benzoin ethyl ether, manufactured by Wako Pure Chemical Industries, Ltd.) was heated at 70°C for 2 hours, cooled to 30°C, and 7 parts by weight of ethylene glycol diglycidyl ether dimethacrylate was added and mixed for 2 hours. Furthermore, 25 parts by weight of "Coronate" (registered trademark) 3015E (ethyl acetate solution of polyisocyanate resin, manufactured by Tosoh Co., Ltd.) and 14 parts by weight of EC-1368 (industrial adhesive, manufactured by Sumitomo 3M Co., Ltd.) were added and mixed to obtain a primer layer composition solution.

[0040] The primer layer composition solution was applied using a bar coater onto a 188 μm-thick "Lumirror" (registered trademark) T60 (polyester film, manufactured by Toray Industries, Inc.) so that the thickness after drying would be 40 μm. The solution was then heated in an oven at 180° C. for 3 minutes to remove the solvent, forming a primer layer.

[0041] 50 parts by weight of "GOHSENOL" (registered trademark) KH-17 (partially saponified polyvinyl alcohol with a saponification degree of 78.5 to 81.5 mol%, weight average molecular weight 165,000, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) were mixed in a mixed solvent of 200 parts by weight of "SOLMIX" (registered trademark) H-11 (alcohol mixture, manufactured by Nippon Alcohol Co., Ltd.) and 200 parts by weight of water at 70°C for 2 hours, and then 1.5 parts by weight of "BLEMMER" (registered trademark) G (glycidyl methacrylate, manufactured by NOF Corporation) was added and mixed for 1 hour. A mixture of 3 parts by weight of "Irgacure" (registered trademark) 651 (benzyl methyl ketal, manufactured by BASF), 21 parts by weight of Epoxy Ester 70PA (acrylic acid adduct of propylene glycol diglycidyl ether, manufactured by Kyoeisha Chemical Co., Ltd.) and 20 parts by weight of ethylene glycol diglycidyl ether dimethacrylate was added and mixed for 90 minutes. The mixture was then cooled to 50°C, after which 0.1 parts by weight of "Megafac" (registered trademark) F-556 (manufactured by DIC Corporation) was added and mixed for 30 minutes to obtain an adhesive layer composition solution.

[0042] The adhesive layer composition solution was applied onto the primer layer using a bar coater so that the thickness after drying would be 30 μm, and the solution was heated in an oven at 160° C. for 3 minutes to remove the solvent, thereby forming an adhesive layer.

[0043] After that, an ultra-high pressure mercury lamp (JP2000T, Oak Manufacturing Co., Ltd.) was used from the adhesive layer side to illuminate the adhesive layer with a cumulative light intensity of 1,000 mJ / cm. 2 The above exposure treatment was carried out to obtain a support composed of an adhesive layer / primer layer / PET film.

[0044] [Formation of photosensitive resin layer] "GOHSENOL" (registered trademark) KL-05 (partially saponified polyvinyl alcohol with a saponification degree of 78.5 to 82.0 mol%, weight average molecular weight 38,000, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) was swollen in acetone, and 1.0 mol% of succinic anhydride was added and stirred at 60°C for 6 hours to add carboxyl groups to the molecular chains. This polymer was washed with acetone to remove unreacted succinic anhydride and dried to obtain a resin having carboxyl groups as anionic groups. The acid value was measured to be 10.0 mgKOH / g.

[0045] Into a three-neck flask equipped with a stirring spatula and a cooling tube, 40 parts by weight of the obtained resin, 30 parts by weight of trimethylolpropane (weight average molecular weight: 134) as a plasticizer, 40 parts by weight of an alcohol mixture ("Solmix" (registered trademark) H-11, manufactured by Japan Alcohol Co., Ltd.) as a solvent, and 60 parts by weight of distilled water were placed, and the mixture was heated at 77°C for 2 hours with stirring to dissolve the resin and plasticizer.

[0046] After the melt was cooled to 70° C., 5 parts by weight of glycidyl methacrylate was added and stirred for 1 hour.

[0047] Next, 10 parts by weight of polyethylene glycol monomethacrylate (monofunctional hydroxyl group, NOF Corporation, "Blenmer" (registered trademark) AE400) and 10 parts by weight of polyethylene glycol dimethacrylate (NOF Corporation, "Blenmer" (registered trademark) AD400), as compounds having an ethylenic double bond, 1.3 parts by weight of benzyl dimethyl ketal as a photopolymerization initiator, and 0.05 parts by weight of 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole as an ultraviolet absorber were added and stirred for 60 minutes to obtain a photosensitive resin layer composition solution.

[0048] [Cover film production for CTP plates] Eleven parts by weight of "GOHSENOL" (registered trademark) KL-05 (partially saponified polyvinyl alcohol with a saponification degree of 78.5 mol% to 82.0 mol%, weight average molecular weight of 38,000, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) were dissolved in 55 parts by weight of water, 14 parts by weight of methanol, 10 parts by weight of n-propanol, and 10 parts by weight of n-butanol to obtain a peeling auxiliary layer composition solution.

[0049] A carbon black dispersion was prepared by kneading and dispersing a mixture of 23 parts by weight of carbon black MA100 (manufactured by Mitsubishi Chemical Corporation), 15 parts by weight of "DIANAL" (registered trademark) BR-95 (an alcohol-insoluble acrylic resin, manufactured by Mitsubishi Rayon Co., Ltd.), 1 part by weight of plasticizer ATBC (acetyl tributyl citrate, manufactured by J-Plus Corporation) and 30 parts by weight of methyl isobutyl ketone in advance using a three-roll mill.

[0050] To the carbon black dispersion, 1 part by weight of AER6071 (epoxy resin, manufactured by Asahi Kasei Chemicals Corporation), 1 part by weight of "U-Ban" (registered trademark) 20SE60 (melamine resin, manufactured by Mitsui Chemicals, Inc.), 0.05 part by weight of Light Ester P-1M (phosphate monomer, manufactured by Kyoeisha Chemical Co., Ltd.), and 100 parts by weight of methyl isobutyl ketone were added and stirred for 30 minutes to obtain a heat-sensitive mask layer composition solution.

[0051] "GOHSENOL" (registered trademark) AL-06 (partially saponified polyvinyl alcohol with a saponification degree of 91 to 94 mol%, weight average molecular weight of 46,500, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) was dissolved in a mixed solvent of water:ethanol = 50:50 (weight ratio) to obtain an adhesion adjusting layer composition solution.

[0052] The peeling auxiliary layer composition solution was applied using a bar coater onto a 100 μm thick polyester film "Lumilar" (registered trademark) S10 (manufactured by Toray Industries, Inc.) so that the thickness after drying would be 0.1 μm, and the coating was dried at 120° C. for 20 seconds to form a peeling auxiliary layer.

[0053] Next, the heat-sensitive mask layer composition solution was applied onto the peeling auxiliary layer using a bar coater so as to give a dried thickness of 1.0 μm, and dried at 140° C. for 20 seconds to form a heat-sensitive mask layer.

[0054] Further, the adhesive strength adjusting layer composition solution was applied onto the heat-sensitive mask layer using a bar coater so that the thickness after drying would be 1.0 μm, and the solution was dried for 20 seconds at 120° C. to form an adhesive strength adjusting layer. In this way, a cover film for a CTP plate, which is a laminate of an adhesive strength adjusting layer / heat-sensitive mask layer / peeling auxiliary layer / protective layer, was obtained.

[0055] [Preparation of flexographic printing plate precursor 1] A mixed solvent of water / ethanol = 50 / 50 (weight ratio) was applied onto the photosensitive resin layer obtained by the method described above, and the cover film for the CTP plate obtained by the method described above was pressed onto the photosensitive resin layer with the adhesion adjustment layer facing the photosensitive resin layer, thereby obtaining flexographic printing plate precursor 1.

[0056] (Production Example 2: Preparation of Flexographic Printing Plate Precursor 2) [Preparation of a support having a primer layer and an adhesive layer] and [Formation of a photosensitive resin layer] were carried out in the same manner as in Production Example 1. A mixed solvent of water / ethanol = 50 / 50 (weight ratio) was applied onto the photosensitive resin layer, and a polyester film "Lumirror" (registered trademark) S10 (manufactured by Toray Industries, Inc.) having a thickness of 100 μm was pressed as a cover film. Next, a high-intensity chemical lamp (TL-K 40W / 10R manufactured by Philips) was used from each of the support side and the cover film side, with an accumulated light amount of 12,000 mJ / cm2 for each. 2 Thus, a flexographic printing plate precursor 2 for engraving was obtained.

[0057] (Production Example 3: Preparation of resin letterpress printing plate precursor) The same procedure as in Production Example 1 was carried out for [Preparation of a support having a primer layer and an adhesive layer].

[0058] "GOHSENOL" (registered trademark) KL-05 (partially saponified polyvinyl alcohol with a saponification degree of 78.5 to 82.0 mol%, weight average molecular weight 38,000, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) was swollen in acetone, and 1.0 mol% of succinic anhydride was added and stirred at 60°C for 6 hours to add carboxyl groups to the molecular chains. This polymer was washed with acetone to remove unreacted succinic anhydride and dried to obtain a resin having carboxyl groups as anionic groups. The acid value was measured to be 10.0 mgKOH / g.

[0059] Into a three-neck flask equipped with a stirring spatula and a cooling tube, 50 parts by weight of the obtained resin, 10 parts by weight of pentaerythritol polyoxyethylene ether as a plasticizer, 50 parts by weight of an alcohol mixture ("Solmix" (registered trademark) H-11, manufactured by Japan Alcohol Co., Ltd.) as a solvent, and 50 parts by weight of distilled water were placed, and the mixture was heated at 90°C for 2 hours with stirring to dissolve the resin and plasticizer.

[0060] After cooling this solution to 70°C, 8 parts by weight of 2-hydroxy-3-phenoxypropyl acrylate, 4 parts by weight of 3-acryloyloxy-2-hydroxypropyl methacrylate, 10 parts by weight of glycerol dimethacrylate, and 6 parts by weight of an acrylic acid adduct of propylene glycol diglycidyl ether as compounds having an ethylenic double bond, 1.3 parts by weight of 2,2-dimethoxy-1,1-diphenylethan-1-one as a photopolymerization initiator, and 0.02 parts by weight of 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole as an ultraviolet absorber were added and stirred for 60 minutes to obtain a photosensitive resin layer composition solution.

[0061] A resin letterpress printing plate precursor was produced by carrying out [Formation of photosensitive resin layer] and [Preparation of cover film for CTP plate] in the same manner as in Production Example 1, except that the obtained photosensitive resin composition solution was used.

[0062] (Manufacturing Example 4: Preparation of Flexographic Printing Plate 1) For flexographic printing plate precursor 1 (14 cm x 30 cm) obtained in Production Example 1, the protective layer of the cover film was peeled off, and the plate was attached to an external drum type plate setter CDI SPARK (manufactured by Esko Graphics Co., Ltd.) equipped with a fiber laser having an infrared light emission region, with the support side in contact with the drum, and a test pattern (having a 10 cm x 10 cm 150 line, 4% halftone dot and a 10 cm x 10 cm solid area) was drawn to form an image mask on the heat-sensitive mask layer.

[0063] Next, using a batch-type exposure and development machine Tomiflex (manufactured by Tomihaku Sangyo Co., Ltd.), the plate was exposed to light at an accumulated light amount of about 16,000 mJ / cm2, and then developed for 60 seconds using tap water adjusted to a temperature of 25°C as the developer. The plate was then dried at 60°C for 10 minutes using an oven. After that, exposure (post-exposure) was performed at an accumulated light amount of 16,000 mJ / cm2 to obtain flexographic printing plate 1. The halftone dots of the obtained flexographic printing plate 1 (150 lines 4% halftone dots formed in an area of ​​1 cm x 1 cm) were observed using a magnifying glass with a magnification of 10x, and no chipping was observed.

[0064] (Production Example 5: Preparation of Flexographic Printing Plate 2) The cover film was peeled off from the flexographic printing plate precursor 2 (14 cm x 30 cm) obtained in Production Example 2, and a test pattern (having 10 cm x 10 cm 150 line 4% dots and 10 cm x 10 cm solid area) was laser engraved using a direct laser engraving system Adflex Direct 250L (manufactured by Comtex Co., Ltd.). Next, using a plate making device DX-A3 (manufactured by Takano Co., Ltd.), the plate was rinsed with tap water at 25°C for 1.5 minutes, and then dried in a hot air dryer at 60°C for 10 minutes to obtain a flexographic printing plate 2. The dots of the obtained flexographic printing plate 2: the 150 line 4% dots formed in an area of ​​1 cm x 1 cm were observed using a magnifying glass with a magnification of 10 times, and no chipping was observed.

[0065] (Production Example 6: Preparation of resin letterpress printing plate) The protective layer of the cover film was peeled off from the resin letterpress printing plate precursor (14 cm x 30 cm) obtained in Production Example 3, and the plate was attached to an external drum-type platesetter CDI SPARK (manufactured by Esko Graphics Co., Ltd.) equipped with a fiber laser with an infrared light emission region, with the support side in contact with the drum, and a test pattern (having a 10 cm x 10 cm 150-line 4% halftone dot and a 10 cm x 10 cm solid area) was drawn to form an image mask on the thermal mask layer.

[0066] Next, a batch-type exposure and development machine, Tomiflex (manufactured by Tomihaku Sangyo Co., Ltd.), was used to develop the film with an integrated light dose of 16,000 mJ / cm. 2 After exposure to light of about 1000 mJ / cm2, the film was developed for 60 seconds using tap water adjusted to 25°C as the developer. The film was then dried in an oven at 60°C for 10 minutes. 2 The resin letterpress printing plate was then exposed (post-exposed) to obtain a resin letterpress printing plate. The halftone dots of the obtained resin letterpress printing plate, 150 lines / 4% halftone dots formed in an area of ​​1 cm x 1 cm, were observed using a 10x magnifying glass, and no chipping was observed.

[0067] The evaluation methods used in each of the Examples and Comparative Examples are shown below.

[0068] (1) Storage stability of processing solution The viscosity of the treatment liquid obtained in each Example and Comparative Example was measured using a Brookfield Digital Viscometer (PV-I Prime). The treatment liquid obtained in each Example and Comparative Example was then placed in a polyethylene bottle and stored for one month under an environment of 25°C and 60% RH. The appearance of the treatment liquid was then visually observed, and the viscosity was measured using the Brookfield Viscometer in the same manner as before storage. Storage stability was evaluated according to the following criteria, with a score of 4 or higher being considered acceptable. 5: No change 4: A very small amount of precipitate is observed. 3: A small amount of precipitate is observed 2: A small amount of precipitate was observed and the viscosity increased. 1: A large amount of precipitate was observed and gelation occurred.

[0069] (2) Printability The flexographic printing plate or resin letterpress printing plate after the treatment obtained in each Example and Comparative Example was mounted on a flexographic printing machine (MPS EF340) equipped with a 991LPI anilox roll. Using UV Flexo Red PHA-LO3 / T&K TOKA, which is an ultraviolet-curing ink, the solid density was adjusted to 1.65, and 20,000m was printed on mirror-coated paper (Oji Tack N Mirror 73 / P22 / G7B, Oji Paper Co., Ltd.) at a speed of 60m / min. The number of print defects in a 10cm x 10cm solid area was observed using a 10x magnifying glass for the prints at 5,000m, 10,000m, and 20,000m. Print defects were evaluated according to the following criteria, and a score of 4 or more at the time of printing 5,000m was considered to be acceptable. 5: Fewer than 5 missing prints 4: The number of printing defects is between 5 and 10. 3: The number of printing defects is between 10 and 15. 2: The number of printing defects is between 15 and 20. 1: There are 20 or more printing defects.

[0070] Example 1 A treatment liquid was obtained by mixing 11.90 parts by weight of TC-300 as a metal chelate compound, 45.48 parts by weight of 2-propanol, and 42.62 parts by weight of water at room temperature. The content of the metal chelate compound in the treatment liquid was 5.0% by weight. The prepared treatment liquid was kept at a temperature of 25°C, and the flexographic printing plate 1 obtained in Production Example 4 was immersed together with the support in the treatment liquid for 10 seconds. The flexographic printing plate was then dried at 50°C for 10 minutes. The results of the evaluation using the above-mentioned method are shown in Table 1.

[0071] Example 2 0.238 parts by weight of TC-300 as a metal chelate compound, 49.910 parts by weight of 2-propanol, and 44.952 parts by weight of water were mixed at room temperature to obtain a treatment liquid. Here, the content of the metal chelate compound in the treatment liquid was 0.1% by weight. Flexographic printing plate 1 was treated with the prepared treatment liquid in the same manner as in Example 1, and evaluation was performed. The results are shown in Table 1.

[0072] Example 3 TC-300 was used as the treatment liquid. The content of the metal chelate compound in the treatment liquid was 42.0% by weight. Flexographic printing plate 1 was treated with this treatment liquid in the same manner as in Example 1, and evaluation was carried out. The results are shown in Table 1.

[0073] Example 4 6.25 parts by weight of TC-400 as a metal chelate compound and 93.75 parts by weight of 2-propanol were mixed at room temperature to obtain a treatment liquid. Here, the content of the metal chelate compound in the treatment liquid was 5.0% by weight. Flexographic printing plate 1 was treated with the prepared treatment liquid in the same manner as in Example 1, and evaluation was performed. The results are shown in Table 1.

[0074] Example 5 6.67 parts by weight of TC-100 as a metal chelate compound and 93.33 parts by weight of 2-propanol were mixed at room temperature to obtain a treatment liquid. Here, the content of the metal chelate compound in the treatment liquid was 5.0% by weight. Flexographic printing plate 1 was treated with the prepared treatment liquid in the same manner as in Example 1, and evaluation was performed. The results are shown in Table 1.

[0075] Comparative Example 1 5.05 parts by weight of TA-8 as a metal alkoxide compound and 94.95 parts by weight of 2-propanol were mixed at room temperature to obtain a treatment liquid. Here, the content of the metal alkoxide compound in the treatment liquid was 5.0% by weight. Flexographic printing plate 1 was treated with the prepared treatment liquid in the same manner as in Example 1, and evaluation was performed. The results are shown in Table 1.

[0076] Comparative Example 2 A treatment liquid was obtained by mixing 5.05 parts by weight of TA-8 as a metal alkoxide compound, 44.95 parts by weight of 2-propanol, and 50.00 parts by weight of water at room temperature. The content of the metal alkoxide compound in the treatment liquid was 5.0% by weight. The prepared treatment liquid was used to treat flexographic printing plate 1 in the same manner as in Example 1, and evaluation was performed. The results are shown in Table 1.

[0077] Example 6 A treatment liquid was prepared in the same manner as in Example 1. The resulting treatment liquid was used to treat and evaluate the flexographic printing plate 2 obtained in Production Example 5 in the same manner as in Example 1. The results are shown in Table 2.

[0078] Example 7 A treatment liquid was prepared in the same manner as in Example 1. The resin letterpress printing plate obtained in Production Example 6 was treated and evaluated using the treatment liquid in the same manner as in Example 1. The results are shown in Table 2.

[0079] Example 8 A treatment liquid was obtained in the same manner as in Example 1. 100 g of the obtained treatment liquid was placed in a paint container (mini roller paint cup, manufactured by Handy Crown Co., Ltd.). After impregnating a 7 mm small roller "Micro Grande" (registered trademark) as a coating roller with the treatment liquid, excess treatment liquid on the coating roller was removed at the liquid squeezing part of the paint container. Then, the treatment liquid was applied to the entire relief surface of the flexographic printing plate 1 obtained in Production Example 4 while rolling an application roller on the relief surface of the flexographic printing plate 1 in the longitudinal direction of the printing plate. The time required for application was 2 seconds. Then, the flexographic printing plate was dried at 50°C for 10 minutes. As a result, a flexographic printing plate without the treatment liquid adhering to the support side of the flexographic printing plate was obtained. The results of the evaluation by the above-mentioned method are shown in Table 2.

[0080] Example 9 Flexographic printing plate 1 was processed and evaluated in the same manner as in Example 8, except that the coating roller was changed to a "Piolas" (registered trademark) sponge roller. The results are shown in Table 2.

[0081]

Table 1

[0082]

Table 2

Claims

1. A processing solution for resin printing plates, which contains a metal chelate compound.

2. The treatment liquid for resin printing plates according to claim 1 , which contains a titanium chelate compound as the metal chelate compound.

3. 3. The treatment liquid for resin printing plates according to claim 2, containing as the titanium chelate compound titanium diisopropoxide bis(triethanol aminate), titanium di-n-butoxide bis(triethanol aminate), titanium diisopropoxide bis(ethylacetoacetate), titanium dihydroxybis(lactate), titanium dihydroxybis(ammonium lactate), titanium aminoethylaminoethanolate and / or titanium(ethylene glycolate) bis(dioctyl phosphate).

4. 4. The processing liquid for resin printing plates according to claim 1, comprising from 0.1% by weight to 50% by weight of the metal chelate compound.

5. 4. A method for producing a resin printing plate, comprising: a step of partially removing a relief-forming layer of a resin printing plate precursor having a relief-forming layer on a support to form a relief; and a step of contacting at least a part of the relief with the treatment liquid for resin printing plate according to any one of claims 1 to 3.

6. The method for producing a resin printing plate according to claim 5, wherein in the step of contacting at least a part of the relief with the treatment liquid for a resin printing plate according to any one of claims 1 to 3, a coating roller is used to contact at least a part of the relief with the treatment liquid for a resin printing plate.

7. A method for producing a printed matter, comprising the steps of obtaining a resin printing plate by the method according to claim 5, depositing ink on the relief, and transferring the ink to a substrate.

8. The method for producing a printed matter according to claim 6, wherein the ink is an ultraviolet-curable ink and / or an electron beam-curable ink.

Citation Information

Patent Citations

  • Method for production of photosensitive resin plate having concave-convex shape or letterpress printing plate, and printing surface treatment solution for use in the method

    WO2008133055A1